Women in Neuromodulation: Innovative Contributions to Stereotactic and Functional Neurosurgery - Heiden, Petra; Pieczewski, Julia; Andrade, Pablo (Frontiers in Human Neuroscience, 2022)
Stereotactic neurosurgery emerged in the mid-20th century following the development of a stereotactic frame by Spiegel and Wycis. Historically women were underrepresented in clinical and academic neurosurgery. There is still a significant deficit of female scientists in this field. This paper aims to demonstrate the career and scientific work of some of the most important women who contributed to the development of stereotactic and functional neurosurgery. Exceptional women from all over the world, represented in this review, assisted the evolution of modern stereotactic and functional neurosurgery as neurosurgeon, neuropathologist, neurologist, neurophysiologist and occupational therapist. Fortunately, we could conclude that, in the last two decades the number of female researches increased significantly.